Analysis of Export Barriers of Honey Pineapple Commodity in Purbalingga Regency - Ayu Fadillah, Sekar; R Indika, Deru (Dinasti Publisher, 2024)
Pineapple production is increasing globally due to the demand for the fruit in the food processing industry to the manufacture of snacks. Purbalingga Regency has not maximized this potential because some MSMEs have stopped and have never exported. This study aims to determine the factors inhibiting the export of honey pineapple commodities inPurbalingga Regency. The technique used was unstructured interviews with 6 resource persons, namely Nanas-qu, Almeidah, the Department of Industry and Trade (Disperindag), the Department of Cooperatives and SMEs (Diskopukm), the FTA Support Center, and export practitioners. The results showed that Honey pineapple MSMEs in Purbalingga Regency struggle to set competitive export prices due to inability to purchase canning machines, reliance on external services, high export costs, and limited negotiation abilities, resulting in low product competitiveness and high selling prices. MSMEs in Purbalingga Regency rely significantly on their own funds for canning machinery, which is insufficient to cover operating expenses. Financial recording constraints limit access to working capital credit programs. Sufficient operating capital is required for operations and annually certificate audits when exporting honey pineapple. Optimal cooperation between pineapple stakeholders and district governments must be done to increase Indonesian pineapple exports to global markets.